Overcoming the protective functions of macrophages by Streptococcus pyogenes virulence factors - I. S. Freydlin; E. A. Starikova; A. M. Lebedeva (Бюллетень сибирской медицины, 2019)
The review is devoted to the analysis of molecular mechanisms of action of S. pyogenes virulence factors aimed at overcoming the protective functions of macrophages. The review describes in detail the main protective functions of macrophages and the mechanisms of their implementation in the course of streptococcal infection. The virulence factors of S. pyogenes, which prevent the recruitment of macrophages to the site of infection, are examined. Particular attention is paid to the analysis of molecular effects that suppress the pathogen by the process of phagocytosis, intracellular bactericidal activity and the production of cytokines by macrophages. The analysis of molecular genetic mechanisms of regulation of the expression of S. pyogenes virulence factors that provide adaptation of the pathogen to changing conditions in the site of inflammation is carried out.